Relationship Between Education Of Toddler Mother And Stunting Events In Posyandu Arumdalu VIII Ngronggah Baru In 2019 - Devi Pramita Sari; Nabilatul Fanny; Rudi Kristyadi (Proceeding of International Conference on Science, Health, And Technology, 2019)
Stunting is a condition of failure to grow to achieve normal growth due to malnutrition in a long period of time. Mother's education is one of the factors causing stunting. The initial preliminary survey revealed that there were 9 respondents out of 15 respondents who were stunted under-five children with a low education in Posyandu Arumdalu VIII Ngronggah Baru. The purpose of this study was to determine the relationship between the education of mothers of children under five with the incidence of stunting in Posyandu Arumdalu VIII Ngronggah Baru. This research was conducted using a descriptive survey with a quantitative method with a cross sectional study approach. The variables of this study are maternal education and the incidence of stunting. The research instrument used questionnaires and respondent identification forms. The population and sample of this study were 36 respondents. The sample technique used is the total sample. Quantitative data analysis uses the chi-square relationship test. The results of this study are based on the results of the Chi-Square test of significance of p between the educational variables of mothers of children under five with the incidence of stunting of 0.004 (p <0.05) then Ho is rejected and there is a relationship. The conclusion is that there is a relationship between the education of mothers of children under five with the incidence of stunting in Posyandu Arumdalu VIII Ngronggah Baru. Suggestions should provide education and knowledge with training and seminars related to stunting through village midwives.